TEACHING CHINESE PHONETICS TO NON-PHILOLOGY STUDENTS - Kim, Olha; Naumenko, Stanislav; Rudaya, Nataliia; Siekina, Nataliia; Zhukova, Kateryna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
China has been promoting the project of the “New Silk Road” (NSR) not just as a revival of the ancient trade road or a transport route between East and West. On a larger scale it is the redesigning of the entire commercial and economic model of the Middle East and Central Asia. Thus we have no time to wait until all the people involved in the project will graduate from the universities’ foreign language departments. We are well aware that we need short term language programs intended for non-philologist learners. One of the aspects that is compulsory for the beginner is the phonetics of the Chinese language. The article discusses the basic modern requirements for the content and form of teaching the phonetics of the Chinese language. The methods like synthesis, comparative analysis and literature review were used to outline the requirements for teaching phonetics of the Chinese language in short term language programs and in higher education. As a result of the study the textbook aimed at forming the correct pronunciation for beginners is introduced. While compiling the textbook the descriptive method and the method of comparison were used.